Clinical referral patterns and cognitive profile in mild cognitive impairment. - Lonie, J; Herrmann, L; Donaghey, C; Ebmeier, K (2008)
BACKGROUND: There is current interest in exploring the different subtypes of mild cognitive impairment (MCI), in terms of both their epidemiology and their cognitive profile. AIMS: To examine the frequency of MCI subtypes presenting to a memory clinic and to document detailed neuropsychological profiles of patients with the amnestic subtype. METHOD: Consecutive tertiary referrals (n=187) were psychiatrically evaluated; 45 patients met criteria for amnestic mild cognitive impairment (aMCI). A subgroup of 33 patients with aMCI as well as 21 healthy controls took part in a thorough neuropsychological examination. RESULTS: Of the patients who were examined in greater neuropsychological detail, ten had pure aMCI (none with visual memory impairment only). Fifteen met criteria for non-amnestic MCI. Fifteen had normal neuropsychological profiles. Using more than one test increased sensitivity to detect episodic memory impairment. CONCLUSIONS: Amnestic MCI is an important diagnosis in secondary and tertiary memory clinics. There is scope to improve the efficacy and sensitivity of the clinical assessment of this impairment.